FUNCTIONAL CLASS OF CHRONIC HEART FAILURE AND DYNAMIC OF HEMODYNAMIC PARAMETERS IN PATIENTS WITH IMPLANTED PACEMAKERS AT THE ANNUAL STAGE OF SUPPORTIVE DRUG THERAPY - Kolomytseva, I. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 2016)
162 patients (89 men and 73 women) aged 69 ± 10 years were observed at the annual stage of supportive drug therapy after implantation of pacemakers in DDD/DDDR, VVI/VVIR and CRT-P/CRT-D modes. Changes of hemodynamic parameters were taken in consideration according to the functional class of chronic heart failure (CHF FC). Pacemakers implantation and supportive drug therapy led to transference of patients to the lower CHF FC with more significant results in CRT-P/CRT-D mode, normalization of heart rate (HR) in all CHF FC and stimulation modes, systolic (SBP) and diastolic blood pressure (DBP) in DDD/DDDR and CRT-P/CRT-D modes, end-systolic and diastolic volumes (EDV and ESV LV), left ventricular ejection fraction (LVEF) in CHF FC II in all stimulation modes and CHF FC III in DDD/DDDR and VVI/VVIR modes and size of the left atrium (LA) in CHF FC II in all stimulation modes and CHF FC I in VVI/VVIR mode. In thickness of posterior wall and interventricular septum of the left ventricle (LV PW and IVS), the sizes of the right atrium (RA) and right ventricle (RV) significant changes in any of CHF FC were not noticed, which requires drug therapy amplification.